Активная Миварная интернет-энциклопедия и развитие миварных сетей на основе многомерных бинарных матриц для одновременной эволюционной обработки более 10 000 правил в реальном времени - Бадалов, А.Ю.; Варламов, О.О.; Санду, Р.А.; Владимиров, А.Н.; Тожа, К.Э. (Штучний інтелект, 2010)
Предложено создать активную Миварную энциклопедию, т.е. мультипредметную экспертную систему с эволюционным наращиванием знаний и активным решением различных задач в реальном времени на основе миварных логико-вычислительных сетей. Для этого требуется описание в едином формализме десятков и сотен тысяч объектов и правил. Для реализации одновременной обработки более 10 000 правил в реальном времени предложены новые пути развития миварных сетей на основе многомерных бинарных матриц. У статті запропонований підхід до створення Міварної активної енциклопедії, яка представляє собою мультипредметну експертну систему з еволюційним нарощуванням знань і активним рішенням різних завдань в реальному часі на основі міварних логіко-обчислювальних мереж. Створення єдиної експертної системи для декількох різних предметних областей (мультипредметна ЕС) вимагає опису в єдиному формалізмі десятків і сотень тисяч об’єктів і правил. Запропоновані нові шляхи розвитку міварних мереж на основі багатовимірних бінарних матриць для реалізації одночасної еволюційної обробки більше десяти тисяч правил в реальному часі. In this paper, an approach to creation of active Mivar encyclopedia, which is a multi-subject-matter expert system
(ES) with the evolutionary capacity of knowledge and active problem solving in real time based on mivar logicalcomputing
networks is developed. Creation of a single expert system for several different domains (multi-subject
EC) requires a description in a unified formalism of tens and hundreds of thousands of objects and rules. Mivar
develops a network of production and the approach used to create various expert systems, and multivariate
evolution applied automated information systems (MEPAIS) support decision-making. To enhance the application
of these formalisms are proposed the new ways of development mivar networks based on multi-dimensional binary
matrices for the implementation of evolutionary concurrent processing of more than ten thousand rules in real time.